2020
DOI: 10.1016/j.annonc.2020.08.2296
|View full text |Cite
|
Sign up to set email alerts
|

LBA6_PR Nivolumab (nivo) plus chemotherapy (chemo) versus chemo as first-line (1L) treatment for advanced gastric cancer/gastroesophageal junction cancer (GC/GEJC)/esophageal adenocarcinoma (EAC): First results of the CheckMate 649 study

Abstract: LBA6 e PR Nivolumab (nivo) plus chemotherapy (chemo) versus chemo as first-line (1L) treatment for advanced gastric cancer/ gastroesophageal junction cancer (GC/GEJC)/esophageal adenocarcinoma (EAC): First results of the CheckMate 649 study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 0 publications
8
168
0
4
Order By: Relevance
“…Nivolumab plus chemotherapy demonstrated superior median OS in the overall population (HR 0.80, 99.3% CI, 0.68-0.94). Of note and as expected, toxicity was higher in the nivolumab plus chemotherapy group (grade 3-4 treatment-related adverse events, 59 vs. 44%) [31]. Taken together, these studies suggest that in selected populations, appropriate combination regimens with IO therapy may overcome therapeutic resistance.…”
Section: Immune Checkpoint Inhibitor Agents In Gastroesophageal Cancesupporting
confidence: 73%
“…Nivolumab plus chemotherapy demonstrated superior median OS in the overall population (HR 0.80, 99.3% CI, 0.68-0.94). Of note and as expected, toxicity was higher in the nivolumab plus chemotherapy group (grade 3-4 treatment-related adverse events, 59 vs. 44%) [31]. Taken together, these studies suggest that in selected populations, appropriate combination regimens with IO therapy may overcome therapeutic resistance.…”
Section: Immune Checkpoint Inhibitor Agents In Gastroesophageal Cancesupporting
confidence: 73%
“…As shown in Table 1 , a total of four phase III studies were included, although KEYNOTE-062 had two evaluable experimental anti-PD-1-based treatment arms (overall: n = 5 experimental arms; n = 4 control arms). 9 , 10 , 11 , 12 , 13 , 14 Two studies were conducted in first-line (KEYNOTE-062; CheckMate-649), one in maintenance (JAVELIN Gastric 100) and one in second-line (KEYNOTE-061). A total of 2545 patients with evaluable MSI status were included and 123 (4.8%) had MSI-high cancers.…”
Section: Resultsmentioning
confidence: 99%
“…The CheckMate-649 first-line study recently showed clinically meaningful and statistically significant OS benefit of nivolumab plus chemotherapy compared with chemotherapy alone in patients with cancers bearing a programmed death-ligand 1 (PD-L1) combined positive score (CPS) ≥5, thus providing robust evidence for the first-line use of anti-PD-1 agents for molecularly selected subgroups inclusive of Western Countries. 13 Although most MSI-high GCs show higher tumor PD-L1 expression versus MSS ones 15 , 16 and may fall in the subgroup with CPS ≥ 5, some may not express PD-L1 at this level and could miss the opportunity of receiving first-line nivolumab. 17 However, patients with MSI-high GC and relatively lower PD-L1 expression could derive less benefit from immunotherapy and future translational studies should focus on the mechanisms of primary resistance to PD-1 blockade in MSI-high cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 In contrast, nivolumab plus chemotherapy significantly improved OS and progression-free survival (PFS) compared with chemotherapy alone in HER2-negative or HER2-unknown patients with CPS ⩾5 in the CheckMate 649 study. 9 Moreover, OS was also prolonged in patients with CPS ⩾1 for all enrolled patients. Based on these results, nivolumab plus chemotherapy will be considered as a new first-line standard treatment in patients with HER2-negative AGC.…”
Section: Introductionmentioning
confidence: 88%